The Effect of Massage Therapy Method, Therapy Duration and Injuries on the Reduction of Pain in Knee Ijuries (Medico Legal Update, 2021)
The aim of the study was to explain the effect of effriction and frirage massage therapy, with a therapyduration of 10 minutes and 15 minutes in helping to reduce movement pain around the injured joint, theinjured joint was the ACL ligament which was injured for 1 month and 2 months but pain in the surroundingmuscles. ACL at the time of massage therapy was still felt by injured patients. This study was an experimentby providing 2 types of therapy, namely effriction and frirage therapy. Each therapy is a combination of twomassage method to get maximum results in reducing pain during flexion and extension of the thigh muscles.With a factorial design with a sample size of 64 people with the criteria to be the sample, namely purposivesampling with injury for 1 month and 2 months. Physical assessment test instruments for pain with an analogvisual scale are used to map changes and decreases in pain before treatment and after therapy and changesin range of motion in the knee to support the healing process assisted by these therapeutic method duringthe effriction massage therapy intervention. Subjective reporting on the level and function of pain is alsodocumented. The results of the study for the homogeneity test mean that the data are homogeneous, andthere is a significant difference between the 1 month and 2 month injuries. It was obtained that for massagetherapy with an effriction treatment, the duration of the injury was 1 month with a duration of 10 minutes oftherapy, which experienced a significant reduction in pain by 0.047 and for effriction therapy with a durationof 15 minutes, it had a significance of 0.049 so that for effriction therapy the duration of the injury was 1month and for frirage therapy the duration of the injury was 1 month. months with 15 minutes of therapy inthis group alone experienced a significant reduction. So that for 1 month there was no interaction betweenthe independent variables and the dependent variable for the duration of 2 months there was an interactionbecause many factors influenced the reduction of pain and must be described in other studies. Effrictionmassage therapy is determined as a complementary therapy that is effective in helping to reduce pain reliefin knee injuries, especially for 1 month injuries with a duration of 10 minutes and 15 minutes and frirage cansignificantly reduce pain in the injury duration of 1 month with a therapy duration of 15 minutes, and thetype for this therapy there was a non-significant reduction in injury duration of 2 months.